Fully Integrated Organic Nanocrystal Diode as High Performance Room Temperature NO2 Sensor. Issue 15 (18th February 2016) - Jalil, Abdur Rehman; Chang, Hao; Bandari, Vineeth Kumar; Robaschik, Peter; Zhang, Jian; Siles, Pablo F.; Li, Guodong; Bürger, Danilo; Grimm, Daniel; Liu, Xingyuan; Salvan, Georgeta; Zahn, Dietrich R. T.; et al.
Abstract : Organic diodes consisting of molecular nano‐pyramid structures sandwiched between metal and strained nanomembrane electrodes are created. The robust and smooth contacts provided by self‐curled metal layers render the molecular nano‐pyramids efficent channels for detecting nitrogen dioxide airflow.